Strategi Pembelajaran Aktif, Kreatif, Inovatif Bidang Studi Pendidikan Agama Islam Berbasis Life Skill (Studi pada Madrasah di Lingkungan Pondok Pesantren): Active, Creative, Innovative Learning Strategies in Islamic Religious Education Based on Life Skills (A Study at Madrasahs in Islamic Boarding School Environments) - Mashudi Mashudi (Fenomena, 2013)
Active, creative, innovative, and enjoyable learning strategies through cognitive, affective, and psychomotor reinforcement are well-known strategies in the education field since 2002. The research problems are as follows: (1) How is the learning organization strategy? (2) How is the learning delivery strategy? and (3) How is the operational learning strategy of active, creative, innovative, and enjoyable learning through cognitive, affective, and psychomotor reinforcement in Islamic religious education subjects based on life skills at madrasahs in Islamic boarding school environments? This research uses a qualitative approach with research locations at two madrasahs around Al Falah Putri Islamic Boarding School in Ampel Wuluban. The results show that the delivery strategy of active, creative, innovative, and enjoyable learning includes all teaching and learning programs aimed at enhancing the activeness of teachers and students. The operational and organizational strategies of both madrasahs involve treating students to develop independence, courage to express ideas, and learning evaluations oriented toward subjects and students. Strategi pembelajaran aktif, kreatif, inovatif, dan menyenangkan melalui penguatan kognitif, afektif, dan psikomotorik merupakan strategi yang telah dikenal dalam bidang pendidikan sejak tahun 2002. Masalah penelitian ini adalah: (1) Bagaimana strategi pengorganisasian pembelajaran? (2) Bagaimana strategi penyampaian pembelajaran? dan (3) Bagaimana strategi operasional pembelajaran dari strategi pembelajaran aktif, kreatif, inovatif, dan menyenangkan melalui penguatan kognitif, afektif, dan psikomotorik dalam bidang studi Pendidikan Agama Islam berbasis life skill di madrasah lingkungan pondok pesantren? Penelitian ini menggunakan pendekatan kualitatif dengan lokasi penelitian di dua madrasah sekitar Pondok Pesantren Al Falah Putri Ampel Wuluban. Hasil penelitian menunjukkan bahwa strategi penyampaian pembelajaran aktif, kreatif, inovatif, dan menyenangkan meliputi seluruh program proses belajar mengajar yang ditujukan untuk meningkatkan keaktifan guru dan siswa. Strategi operasional dan pengorganisasian di kedua madrasah memberikan perlakuan kepada siswa untuk memiliki kemandirian, keberanian mengemukakan ide, serta evaluasi pembelajaran yang berorientasi pada mata pelajaran dan siswa.